Bilateral lung transplantation for Castleman disease with end‐stage bronchiolitis obliterans. Issue 1 (21st October 2021) - Yue, Bingqing; Huang, Jian; Jing, Lei; Yu, Huaqing; Wei, Dong; Zhang, Ji; Chen, Wenhui; Chen, Jingyu
Abstract: Bronchiolitis obliterans (BO) is a severe complication of Castleman disease (CD), a rare lymphoproliferative disease with unclear pathogenesis. Currently, there are no reports on the safety or outcomes of bilateral lung transplantation in patients with BO due to CD. This study aimed to characterize the clinical manifestations and features of BO and CD. We retrospectively analyzed the medical records of six consecutive patients with BO and CD who underwent bilateral lung transplantation between December 2012 and December 2020. The average age of patients at lung transplantation was 33 ± 15 years, and the age range of patients at diagnosis of CD was about 9–56 years. The body mass index was 15.2 ± 1.9 kg/m 2 . The average time from diagnosis to lung transplantation was 4.1 ± 2.7 years. All the patients had unicentric CD (UCD); five had concomitant paraneoplastic pemphigus, and four received extracorporeal membrane oxygenation during surgery. The average hospital stay was 51 ± 53 days. Infection was the most common postoperative complication. CD did not recur in any of the patients. Thus, bilateral lung transplantation is a viable and safe treatment for selected patients with CD and BO, which can improve the quality of life and prolong survival.